Ministry of Manpower Decree No. 146 of the Year 2019 With Regard to the Conditions and Procedures of Granting Foreigners Work Permits = وزارة القوى العاملة قرار رقم 146 لسنة 2019 بشأن شروط وإجراءات الترخيص بالعامل للأجانب - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic